2020
DOI: 10.1111/apt.16077
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: prevalence, progression rates and mortality predictors of non‐alcoholic fatty liver disease reflected by German statutory health insurance data

Abstract: LINKED CONTENTThis article is linked to Canbay et al paper. To view this article, visit https://doi.org/10.1111/apt.16016

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…These findings were similar to those reported in a study using RWD in Germany that reported the prevalence of NAFLD/NASH as 4.7% (215 655 out of 4 580 434 patients in the database) 41 . It is possible that patients with an ICD‐10 diagnosis code for NAFLD/NASH represent those with more advanced cases than in the broader population, which would also explain the higher than expected prevalence of ACLD/cirrhosis noted in our study 42 …”
Section: Discussionsupporting
confidence: 92%
“…These findings were similar to those reported in a study using RWD in Germany that reported the prevalence of NAFLD/NASH as 4.7% (215 655 out of 4 580 434 patients in the database) 41 . It is possible that patients with an ICD‐10 diagnosis code for NAFLD/NASH represent those with more advanced cases than in the broader population, which would also explain the higher than expected prevalence of ACLD/cirrhosis noted in our study 42 …”
Section: Discussionsupporting
confidence: 92%